THE EFFECT OF EMPLOYEE TRAINING ON WORK PRODUCIVITY AT PT BRINGIN GIGANTARA - Ilyas Kamaludin; Syamsurizal Syamsurizal; Utep Sobali (POLITEKNIK LP3I JAKARTA, 2026)
This study aimed to examine the effect of employee training on employee work productivity using a quantitative approach. The independent variable in this study was Employee Training, while the dependent variable was Employee Work Productivity. The research was conducted at PT Bringin Gigantara with a sample consisting of 60 employees from the Service Division and the Resource Management Division (PSD), specifically in the policy section. The sampling technique applied was Non-Probability Sampling using the Total Sampling method. Data were collected through a digital questionnaire distributed via Google Forms and analyzed using SPSS version 27. The results indicated that Employee Training significantly affected Employee Work Productivity. This finding was supported by an Adjusted R Square value of 0.153, equivalent to 15.3%, indicating that the Employee Training variable (X) explained approximately 15.3% of the variance in Employee Work Productivity (Y), while the remaining 84.7% was influenced by other factors outside the scope of this study. Furthermore, the hypothesis testing result showed a t-count value of 3.240, which was greater than the t-table value of 1.671, with a p-value of 0.002, lower than the significance level of α = 0.05.